Price Guarantees, Consumer Search, and Hassle Costs - Ulrich Schwalbe; Pio Baake (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The paper deals with the competitive effects of price guarantees in a spatial duopoly where consumers can search for lower prices but have to incur hassle costs if they want to claim a price guarantee. It is shown that symmetric equilibria with and without price guarantees exist but price guarantees will have no effect on prices if search costs are low, hassle costs are high and the number of uninformed consumers is small. However, when both firms use price guarantees, there also exist payoff-dominant equilibria where both firms use mixed pricing strategies in the form of "high-low" pricing schemes, provided that the search costs are sufficiently high.
Keywords: D43; L13; C72; 330